Thermoendocrine Influences on the Duration of Mother-Litter Contact in the Norway Rat - Woodside, Christine Barbara (My University, 1978)
During the first two weeks postpartum, the lactating Norway rat shows a gradual decline in the amount of time that she spends in contact with her litter. This decline results from a gradual decrease in the duration of individual nest bouts rather than in their frequency. This normal nesting pattern is disrupted following adrenalectomy-ovariectomy (Adex-Ovex) and prolactin suppression (Leon, Croskerry & Smith, 1978). Since the effects on nesting behaviour produced by these manipulations are accompanied by a decrease in maternal core temperature it has been suggested that the normally elevated core temperature of lactating dams renders them vulnerable to an acute rise in temperature during a nest bout and the dam terminates the nest bout to maintain her thermal homeostasis.
The purpose of this dissertation was to: 1) identify those hormones sufficient to maintain normal nest time; 2) determine the mode of action of those hormones and 3) determine the relative importance of thermal factors in limiting nest bout duration at different stages postpartum. Glucocorticoids were identified as sufficient adrenal factors to reinstate the normal nesting pattern and body temperature of Adex-Ovex dams. Moreover, hormone-replaced females had the normal, additional rise in temperature during Day 10 nest bouts, whereas Adex-Ovex females did not. These data not only support the notion that a rise in dam core temerature during a nest bout produces bouts of shorter duration but they also indicate that the elevated core temperature typical of lactating dams makes them vulnerable to the acute thermal effects of huddling.
Prolactin-suppressed dams show a halt in the decline in daily nest time in the second week postpartum which is accompanied by a reduction in material core temperature. It has been suggested that the effects of prolactin suppression, are mediated by a consequent depression in corticosterone levels, rather than a direct effect of the absence of prolactin (Leon, Groskerry & Smith 1978). Experiments described in this thesis show that, as predicted, corticosterone replacement in prolactin-suppressed dams reinstated a normal decline of daily nest time and increases their core temperature. However, corticosterone may act by compensating for some of the metabolic actions of prolactin, because prolactin-suppressed dams actually had increased levels of circulating corticosterone.
Reinstatement of material heat load by warming the maternal huddles reinstated normal patterns of nesting behaviour in Adex-Ovex and prolactin-suppressed dams. Indeed, warmed Adex-Ovex dams had an acute rise in core temperature during nest bouts, similar to that seen in intact dams.
The question of the relative importance of thermal cues in inducing nest bout termination at different stages postpartum was determined by comparing the changes in core temearature that dams experienced during nest bouts in the first and then the second week postpartum. Thermal factors played little role in limiting the nest bouts of Day 4 dams, but by Day 10, the percentage of nest bouts during which dams experienced a rise in core temperature had increased to 95%. Moreover, the rate of increase in material core temperature during a Day 10 nest bout was significantly greater than that experienced on Day 4.
The data obtained indicate 1) glucocorticoids plus prolactin are sufficient to maintain the normal pattern of nesting behaviour in the lactating rat; 2) hormonal influences on nest time are thermally mediated; 3) thermal factors increase their contribution to the limitation of mother-litter contact over the first two weeks postpartum such that they result in the gradual decline in daily nesting time that is typical of this species.
Keywords: Psychology; Psychology